2020
DOI: 10.7759/cureus.9981
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Culture-Negative Versus Culture-Positive Sepsis and Outcomes of Patients Admitted to the Pediatric Intensive Care Unit

Abstract: Background Sepsis remains a major cause of death, with high mortality and morbidity rates in children. The cause of mortality may be associated with several factors, including differences in cultures and the type of organism. This study was aimed at evaluating the characteristics and outcomes of negative bacterial blood culture compared to those of positive bacterial blood culture in children with severe sepsis/septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…2016 All-cause Single-center, retrospective cohort study 80 42 38 Kethireddy et al [ 19 ] 2018 Canada, USA, Saudi Arabia Jan. 1997–Dec. 2010 Hospital Multicenter, retrospective cohort study 8670 2651 6019 Sigakis et al [ 20 ] 2019 USA Jan. 2007–May 2014 Hospital Single-center, retrospective cohort study 10,393 9288 1105 Hazwani et al [ 21 ] 2020 Saudi Arabia Apr. 2015–Jan.…”
Section: Resultsmentioning
confidence: 99%
“…2016 All-cause Single-center, retrospective cohort study 80 42 38 Kethireddy et al [ 19 ] 2018 Canada, USA, Saudi Arabia Jan. 1997–Dec. 2010 Hospital Multicenter, retrospective cohort study 8670 2651 6019 Sigakis et al [ 20 ] 2019 USA Jan. 2007–May 2014 Hospital Single-center, retrospective cohort study 10,393 9288 1105 Hazwani et al [ 21 ] 2020 Saudi Arabia Apr. 2015–Jan.…”
Section: Resultsmentioning
confidence: 99%
“…61 The gold standard for diagnosing sepsis is blood culture, however, cultures can take hours to days to yield results and up to 87% of pediatric sepsis cases are blood culture-negative. 62,63 A benefit to metabolomics is that very small volume samples can be analyzed in less than an hour. 6 One of the earliest studies that used metabolomics for pediatric sepsis focused on differentiating between septic shock and systemic inflammatory response syndrome (SIRS) and predicting mortality (Table 4).…”
Section: Pneumoniamentioning
confidence: 99%
“…The search strategy identi ed 235 studies, and the data were from seven cohort studies comprising 22655 patients (Table 2) [16][17][18][19][20][21][22]. The characteristics of the included studies are shown in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%